Propuesta para la expedición de una ordenanza para el uso obligatorio de bolsas plásticas biodegradables en el Distrito Metropolitano de Quito - Mata Carrillo, Andrea Patricia (2012)
The dynamism of the modern world is reflected in the significant population growth, consumption habits of the population and supply and demand for goods and services, with the consequent need for producers, manufacturers, retailers and distribution centers to provide increasingly and greater convenience to its customers or users. In the environment of the active relationship of supply and demand of goods and services, spend huge amounts of resources and raw materials – up to the time of delivery or main product purchased, such as packaging, accessories, and especially plastic bags or other materials that allow each of transporting goods purchased by final consumers